Unraveling the future productivity burden of cardiovascular disease in Qatar: Investigating the modifiable risk factors control in type 2 diabetes - Dina Abushanab; Daoud Al-Badriyeh; Danny Liew; Zanfina Ademi (American Journal of Preventive Cardiology)
Aims: Insufficient risk factor control can lead to a loss of millions of productivity-adjusted life years (PALYs). We aimed to assess the productivity burden of cardiovascular disease (CVD) in type 2 diabetes (T2D) and examine the potential advantages of enhancing the control of modifiable CVD risk factors in Qatar. Materials and methods: Models were developed to quantify the productivity burden, in terms of PALYs, of CVD in Qataris with T2D, aged 40–65 years, from 2024 to 2033. The financial value of PALYs was determined based on the gross domestic product (GDP) per full-time worker (i.e. US$80,573). The base-case model estimated the productivity burden of CVD, and interventional scenarios were simulated to assess potential gains resulting from improved control of modifiable risk factors, including reduced incidence of T2D, lower systolic blood pressure (SBP), decreased number of smokers, and reduced total cholesterol. All costs and outcomes were discounted at an annual rate of 3 %. Results: The base-case analysis projected that CVD in T2D would result in an estimated 2,096,536 PALYs (95 % confidence interval, 1,689,272–2,182,939), contributing US$225.46 (95 %CI, 1,689,272–2,182,939) billion to the country's GDP. However, implementing interventions to decrease the T2D incidence, lower SBP, reduce the number of smokers, and improve the total cholesterol could yield gains of 200,408, 198,173, 194,725, and 113,462 PALYs, respectively. These improvements would also lead to economic gains of US$20.01 billion, US$20.17 billion, US$19.78, and US$12.79 billion, respectively. Conclusions: Implementing interventions that prioritize risk factor control and prevention of CVD can help enhance overall productivity in the country.